Implementation of SIGA Application as Gender Data Access to Realizing Agile and Digital Governance (Agile Governance and Innovation Measurement Journal, 2024)
The Special Region of Yogyakarta (DIY) in order to realize an inclusive and women- friendly province created a gender application based on the Gender and Child Information System (SIGA). The purpose of the SIGA application is to record gender data quickly, precisely and accurately in DIY. In the concept of Agile Governance, speed and accuracy are needed to produce accurate gender data presentation to the community. Based on this, this research aims to analyze the SIGA application as an access to data search in the Special Region of Yogyakarta. The approach in this research uses a qualitative method with a case study approach. The main data was obtained from secondary data through online media and scientific articles relevant to the topic studied. Data analysis was conducted interactively with the help of NVIVO 12 plus software through the Crosstab Analysis feature. The theoretical foundation in this research uses three principles from Agile Governance theory, including: First, Based on Quick Wins; Second, Systematic and Adaptive Approach, and Simple Design and Continous Refinement. So that the results of the study can show the speed and accuracy of the SIGA application, data updates, ease of access, and features that can be accessed easily for the public in finding gender data in DIY. Keywords: : SIGA Application; Agile Governance; Gender